2016
DOI: 10.1371/journal.pone.0147039
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Human Salivary Microbiomes—Insights into the Novel Characteristics of Microbial Community Structure in Caries and Caries-Free Subjects

Abstract: Recently, high-throughput sequencing has improved the understanding of the microbiological etiology of caries, but the characteristics of the microbial community structure in the human oral cavity with and without caries are not completely clear. To better understand these characteristics, Illumina MiSeq high-throughput sequencing was utilized to analyze 20 salivary samples (10 caries-free and 10 caries) from subjects from the same town in Dongxiang, Gansu, China. A total of 5,113 OTUs (Operational Taxonomic U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 60 publications
9
53
0
Order By: Relevance
“…Furthermore, we found that the genus Scardovia , which was newly recognized as cariogenic bacteria involved in the later stage of severe early childhood caries [29], was significantly more frequently detected in the caries-affected group than in the caries-free group, with a low relative abundance in the total sequences. This finding is consistent with that of a previous study [30]. …”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, we found that the genus Scardovia , which was newly recognized as cariogenic bacteria involved in the later stage of severe early childhood caries [29], was significantly more frequently detected in the caries-affected group than in the caries-free group, with a low relative abundance in the total sequences. This finding is consistent with that of a previous study [30]. …”
Section: Discussionsupporting
confidence: 94%
“…In comparison with caries‐active individuals, caries‐free and/or periodontally healthy individuals exhibit a greater diversity of bacterial populations (Li, Ku, Xu, Saxena, & Caufield, ). In this study, the average number of detected OTUs per patient was 8,885, which is in agreement with previous reports about adult saliva microbiotas (Zhou et al, ). As shown in Figures , the alpha diversity, which reflects internal biodiversity, and the beta diversity, which represents the variation in microbial community structure, all showed no significant difference between Group B and Group P. Hence, the general biodiversity and microbial community structure did not change significantly six months after the Invisalign procedure.…”
Section: Discussionsupporting
confidence: 93%
“…High‐throughput technologies based on 16S rRNA gene sequencing have been widely used in bacterial phylogeny and taxonomy studies due to the highly conserved, omnipresent, and large‐volume (1,500 bp) characteristics of the 16 rRNA gene (Janda & Abbott ). Illumina MiSeq high‐throughput sequencing is one of the cutting‐the‐edge techniques for microbial community analysis, considering its advantages in accuracy, coverage, sequencing depth, and low cost, and it has been increasingly used in the investigation of the oral microbiome in different diseases (Wang et al, ; Zhou et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Dielma fastidiosa was reported in the human gut (Ramasamy, Lagier, Nguyen, Raoult, & Fournier, ). The relative abundance of Scardovia was significantly higher in the salivary samples in the group with caries (Zhou et al., ). Scardovia wiggsiae was associated with the elevated sugar intake (Keller, Kressirer, Belstrøm, Twetman, & Tanner, ).…”
Section: Discussionmentioning
confidence: 97%